The Name of God on Trial: Narratives of law, religion and state in Malaysia - Joshua Neoh (Law Text Culture, 2014)
The power to name is both an awesome and awful power – it is an exercise of sovereign power. In the Abrahamic religions, the monotheistic God is the ultimate sovereign. The power to name God, then, is one of the most magnificent powers that is conceivable to humans: it is the sovereign power to name the ultimate sovereign. It is this naming of God that has been put on trial in Malaysia. The state decrees that the name ‘Allah’ is only to be used in reference to the Islamic God. Christians, in response, have insisted that the state has no monopoly over the power to name God, and they too should be able to call their God – the Christian God – by the name of ‘Allah’. The matter ends up in court, where judges are asked to decide on the name of God. This case raises a perplexing puzzle: how on earth did the human judges in Malaysia end up with the power to name the divine judge?